Kemampuan Mahasiswa Praktikan PPPL Jurusan PGMI Fakultas Tarbiyah Dan Keguruan IAIN Antasari dalam Penggunaan Strategi Pembelajaran di MI Al Muhajirin Banjarmasin - Salmah, Syarifah (Khazanah: Jurnal Studi Islam dan Humaniora, 2014)
Learning strategy is an important factor in improving the quality of learning . In connection with the use of learning strategies , teachers need to be careful in the selection of strategies that will be used . This study aimed to describe the use of learning strategies by students on field practice MI Muhajirin Banjarmasin . Data was collected by observation . The analysis used is descriptive qualitative approach . Based on the analysis of data obtained from this study , it can be concluded that the ability to use learning strategies maahasiswa PPL II participants in MI Al Muhajirin can be quite good.Key words : Learning strategy and practice to teaching